RESPONS PERTUMBUHAN DAN PRODUKSI SORGUM (Sorghum bicolor (L.) Moench) TERHADAP PEMBERIAN FUNGI MIKORIZA ARBUSKULA (FMA) DAN KOMPOS KASCING - Junita P Napitupulu; T.Irmansyah T.Irmansyah; Jonis Ginting Jonis Ginting (Universitas Sumatera Utara, 2013)
Response of growth and yield of sorghum (Sorghum bicolor (L.) Moench) by giving of arbuskulamycorrhiza fungi (FMA) and vermicompost. Sorgum is one of the important food crops in theworld. Most of its yield is used as food, beverages, animal feed, and industrial needs. Increasingof degraded land area and land degradation rate that being higher, so that it needs to improvesoil condition and enchance plant growth by using of FMA andvermicompost. The aim of thisresearch was to obtain the right dosage of FMA and vermicompost for growth and yield of sorgum(Sorghum bicolor (L) Moench.). The research was conducted in the field UPT BBI in the TanjungSelamat village of Sunggal sub-district, Deli Serdang regency in North Sumatra, in May to August2012, using a randomized block design (RBD) factorial with two factors and three replications . Thefirst factor is the dosage of FMA (0, 5, 10 g / plant). The second factor is the dosage ofvermicompost (0, 30, 60, 90 g / plant). The results showed that FMA significantly affect on plantheight, number of leaves, and the degree of root infection. Vermicompost significantly affect onplant height and number of leaves. Interaction between the giving of FMA and vermicompostsignificantly affect on the degree of root infection.